Prepregnancy maternal body mass index and venous thromboembolism: a population‐based cohort study. (19th December 2018) - Butwick, AJ; Bentley, J; Leonard, SA; Carmichael, SL; El‐Sayed, YY; Stephansson, O; Guo, N
Abstract : Objective: To assess the relation between maternal body mass index (BMI) and pregnancy‐related venous thromboembolism (VTE). Design: Cohort study. Setting and population: A total of 2 449 133 women with singleton pregnancies who underwent delivery hospitalisation in California between 2008 and 2012. Methods: Association of pre‐pregnancy BMI and the risk of an antepartum and postpartum VTE was examined using logistic regression, with normal BMI as reference. Main outcome measures: Antepartum and postpartum VTE‐related hospitalisation. Results: The prevalence of antepartum and postpartum VTE increased with increasing BMI (antepartum: 2.3, 3.0, 3.8, 4.2, 4.7, and 10.6 per 10 000 women for underweight, normal BMI, overweight, obesity class I, II, and III, respectively, P < 0.001; postpartum: 2.0, 3.1, 3.9, 5.6, 9.0, and 13.2 per 10 000 women, P < 0.01). The adjusted odds of antepartum and postpartum VTE increased progressively with increasing BMI, with obesity class III women having the highest risk of pregnancy‐related VTE compared with normal BMI women: adjusted odds ratio for antepartum VTE: 2.9; 95% CI 2.2–3.8 and adjusted odds ratio for postpartum VTE: 3.6; 95% CI 2.9–4.6. Conclusions: Our findings clearly demonstrate an increasing risk of pregnancy‐related VTE with increasing BMI. Tweetable abstract: Obesity was associated with increased odds of antepartum and postpartum venous thromboembolism. Tweetable abstract: Obesity was associated with increased odds of antepartum and postpartum venous thromboembolism.